Fiber Bragg gratings - Kashyap, Raman (San Diego : Academic Press, 1999)
Optical fibers have revolutionized telecommunication, becoming the most widely used and the most efficient device for relaying information over long distances. While the market for optical fiber continues to grow, the next stage in the field of communication is the mass delivery of integrated services, such as home banking, shopping, internet services, and entertainment using video on demand. The economies and performance potential will determine the type of technology likely to succeed in the provision of these services. But it is already clear that optical fibers will play a crucial role in communication systems of the future. The opportunities provided by fiber Bragg gratings are of enormous importance for the further development of the fiber optic communication lines as cost-effective and efficient devices of the future. Fiber Bragg Gratings is the result of a growing demand for focused and reliable information on the subject. It brings together the fundamentals of fiber gratings, their specific characterizations, and numerous applications. In addition to researchers, scientists, and graduate students, it will be of interest to industrial practitioners in the field of fabrication of fiber optic materials and devices. It begins with the principles of fiber Bragg grating, from photosensitization of optical fibers, Bragg grating fabrication, theory, properties of grating, specific application, and concludes with measurement techniques. * Addresses one of the most promising fields for future development in applied optics * First book ever on the subject of fiber Bragg gratings * Written by a pioneer in the field of optical communications * Covers topics important to both research and industry * Discusses theory, practical applications, and measurement.
Forward. Preface. Introduction. Photosensitivity and Photosensitization of Optical Fibers. Fabrication of Bragg Gratings. Theory of Fiber Bragg Gratings. Apodisation of Fiber Gratings. Fiber Grating Band-Pass Filters. Chirped Fiber Bragg Gratings. Fiber Grating Lasers and Amplifiers. Measurement and Characterization of Gratings. Index.
Includes bibliographical references and index.
Keywords: Optical fibers; Bragg gratings; Optical detectors; Electronic books